Deep learning based approach for automated characterization of large marine microplastic particles. (January 2023) - Han, Xiao-Le; Jiang, Ning-Jun; Hata, Toshiro; Choi, Jongseong; Du, Yan-Jun; Wang, Yi-Jie
Abstract: The rapidly growing concern of marine microplastic pollution has drawn attentions globally. Microplastic particles are normally subjected to visual characterization prior to more sophisticated chemical analyses. However, the misidentification rate of current visual inspection approaches remains high. This study proposed a state-of-the-art deep learning-based approach, Mask R–CNN, to locate, classify, and segment large marine microplastic particles with various shapes (fiber, fragment, pellet, and rod). A microplastic dataset including 3000 images was established to train and validate this Mask R–CNN algorithm, which was backboned by a Resnet 101 architecture and could be tuned in less than 8 h. The fully trained Mask R–CNN algorithm was compared with U-Net in characterizing microplastics against various backgrounds. The results showed that the algorithm could achieve Precision = 93.30%, Recall = 95.40%, F1 score = 94.34%, AP bb (Average precision of bounding box) = 92.7%, and AP m (Average precision of mask) = 82.6% in a 250 images test dataset. The algorithm could also achieve a processing speed of 12.5 FPS. The results obtained in this study implied that the Mask R–CNN algorithm is a promising microplastic characterization method that can be potentially used in the future for large-scale surveys. Graphical abstract: Image 1 Highlights: Mask R–CNN algorithm was implemented to characterize large marine microplastics. The algorithm could locate, classify, segment, and enumerate microplastics. Microplastics could be automatically classified as fiber, fragment, pellet, and rod.